Elastoplastic and nonlinear analysis of functionally graded axisymmetric shell structures under thermal environment, using a conical frustum finite element model - Simões Moita, José Mateus (2020)
This work presents the formulation for static bending analysis of functionally graded axisymmetric plate/shell type structures under mechanical loading, and considering different structural behaviours: linear, geometric nonlinear and material nonlinear. The implemented model is based on a simple conical frustum finite element with 2 nodes, and 3 degrees of freedom per node, which includes shear deformation effects, and it shows to be extremely efficient in the analysis of axisymmetric shells subjected to axisymmetric loading. The used of reduced numerical integration procedure is essential for its success when applied to thin shells. The formulation accounts for the calculation of displacements and through-thickness stress distribution. The solutions for some illustrative examples involving variation of volume fractions are obtained, and the results are presented and compared with numerical alternative models when available, and discussed.